The I/O consultant advice and insights for building a successful career (American Psychological Association, 2008)
"Consulting is one of the fastest growing occupations in the United States. This innovative volume offers basic guidance on the fundamentals of consulting, with authoritative essays by leaders in the field. Hedge and Borman and their colleagues guide their readers through a career continuum, beginning with learning about potential employers to creating and maintaining a business and watching it grow and thrive. In chapters that combine a strong grounding in contemporary industrial and organizational (I/O) research with personal accounts of their career journeys and day-to-day activities, the contributors bring the basic principles conveyed by Hedge and Borman to life. Readers hear of the extraordinary breadth of consulting experiences--in the private and public sectors, the military, and academia. The authors consider such topics as strategic planning, points of entry into the field, ethics and networking, and the advantages and disadvantages of joining a large firm versus starting up one's own consulting practice. The principles and perspectives detailed in this book will resonate with psychology graduate students embarking on their careers as well as seasoned professionals weighing new career directions"--Jacket. (PsycINFO Database Record (c) 2008 APA, all rights reserved)